The Response of Orthotropic Steel Decks to Traffic Loads - Dempsey, A.T.; Keogh, D.L.; Jacob, B.; Carracilli, J. (Engineering Transactions, 2000)
This paper describes the instrumentation and load testing of a three-span orthotropic steel bridge in France. Strain gauges were attached to the underside of the orthotropic plate to measure the dynamic response of the bridge to traffic loading. Two preweighed trucks were driven across the bridge at different velocities to investigate the influence of truck speed on the dynamic amplification of the bridge. A model suitable for the prediction of the dynamic response of the bridge is described. This consists of an elaborate finite element model to determine the natural frequencies and mode shapes of the bridge, and a dynamic model which uses this information to determine the dynamic response. The results of the experimentation are presented and the relationship between truck speed and dynamic amplification are shown. Finally, the loads applied to the bridge by an instrumented truck driving over it are presented and comparisons are made with the loads applied at the bridge approaches.